THE EFFECT OF INTERNAL CONTROL SYSTEMS, HUMAN RESOURCE COMPETENCIES, AND UTILIZATION OF INFORMATION TECHNOLOGY ON THE QUALITY OF FINANCIAL STATEMENTS IN COOPERATIVES IN JAMBI CITY - Juniar, Diaz Vilda; Rahayu, Sri; Hernando, Riski (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This research focused on investigating the effects of the internal control system, human resource competencies, and the use of information technology on the standard of financial reports in cooperatives in Jambi City. The independent variables examined were the internal control system, human resource competencies, and information technology usage, with the dependent variable being the standard of financial statements. The analysis employed included exploratory data analysis, standard assumption assessments, and hypothesis assessment using IBM SPSS version 20. The findings indicated that the internal control system had no significant effect, whereas human resource competencies and the utilization of information technology positively influenced the standard of financial statements. Keywords: Internal Control Systems; Human Resource Competencies; Information Technology Utilization; Quality of Financial Statements